Defining early carcinogenic markers for the prediction of the hazard potential of mineral fibres in an in vitro human 3D bronchial model - Vanessa Almonti; Serena Mirata; Mario Passalacqua; Stefania Vernazza; Sara Tirendi; Sara Ferrando; Beatrice Risso; Elena Grasselli; Giulia De Negri Atanasio; Anna Maria Bassi; Alessandro F. Gualtieri; Sonia Scarfì (Archives of Toxicology, 2026)
This study aimed to identify early carcinogenic markers to predict the hazard potential of mineral fibres using a human 3D bronchial model. Traditional 2D cell models inadequately mimic lung complexity, prompting the use of more physiologically relevant 3D systems. We investigated the effects of crocidolite (CRO) and two size fractions of chrysotile (≤ and > 5 μm length: CHR S and CHR L) to elucidate early toxicological mechanisms and relate them to the IARC key characteristics (KCs) of carcinogens. Initial analyses (MTT, TEER, and histology) at 24–48 h showed a transient acute toxicity and tissue resilience, indicating limited predictive value at this time point. However, after 12 d of exposure, fibre-treated tissues exhibited persistent alterations corresponding to established IARC KCs, suggesting the early onset of cell transformation pathways. Key findings included: sustained inflammatory signalling, characterized by prolonged overexpression of IL-1β, IL-6, and IL-8; ii) persistent genotoxicity, marked by the prolonged nuclear positivity of γH2AX, indicating DNA double-strand breaks without significant cell death; and iii) induction of fibrotic and epithelial-to-mesenchymal transition (EMT) signals, including the increased expression of key markers such as TGF-β, VEGF, ZEB-2, N-Cadherin, Vimentin, and Mesothelin. These alterations correspond to IARC KCs 2, 6, and 8. They were observed within a short time frame of tissue treatment and could serve as reliable, early predictive endpoints for in vitro toxicological tests. We propose that integrating these specific KC-based biosignatures in 3D lung models with physicochemical fibre characterization may provide a robust framework for predictive assessment of inhalable fibre carcinogenicity.

In vitro testing of hazardous mineral fibres: The issue of the concentration metric - Alessandro F. Gualtieri; Serena Mirata; Mario Passalacqua; Anna Maria Bassi; Sonia Scarfì (Environmental Toxicology and Pharmacology, 2025)

Toxicity of size separated chrysotile fibres: The relevance of the macrophage-endothelial axis crosstalk - Serena Mirata; Vanessa Almonti; Mario Passalacqua; Stefania Vernazza; Anna Maria Bassi; Dario Di Giuseppe; Alessandro F. Gualtieri; Sonia Scarfì (Toxicology, 2025)

Sphingolipids and plasma membrane hydrolases in human primary bronchial cells during differentiation and their altered patterns in cystic fibrosis - Nicoletta Loberto; Giulia Mancini; Rosaria Bassi; Emma Veronica Carsana; Anna Tamanini; Nicoletta Pedemonte; Maria Cristina Dechecchi; Sandro Sonnino; Massimo Aureli (Glycoconjugate Journal, 2020)
Human primary bronchial epithelial cells differentiated in vitro represent a valuable tool to study lung diseases such as cystic fibrosis (CF), an inherited disorder caused by mutations in the gene coding for the Cystic Fibrosis Transmembrane Conductance Regulator. In CF, sphingolipids, a ubiquitous class of bioactive lipids mainly associated with the outer layer of the plasma membrane, seem to play a crucial role in the establishment of the severe lung complications. Nevertheless, no information on the involvement of sphingolipids and their metabolism in the differentiation of primary bronchial epithelial cells are available so far. Here we show that ceramide and globotriaosylceramide increased during cell differentiation, whereas glucosylceramide and gangliosides content decreased. In addition, we found that apical plasma membrane of differentiated bronchial cells is characterized by a higher content of sphingolipids in comparison to the other cell membranes and that activity of sphingolipids catabolic enzymes associated with this membrane results altered with respect to the total cell activities. In particular, the apical membrane of CF cells was characterized by high levels of ceramide and glucosylceramide, known to have proinflammatory activity. On this basis, our data further support the role of sphingolipids in the onset of CF lung pathology.

Isolation and characterization of chloroplast Photosystem II antenna of spinach by reversed-phase liquid chromatography - Lello Zolla; Anna Maria Timperio; Maria Grazia Testi; Maria Bianchetti; Roberto Bassi; Francesco Manera; Danilo Corradini (Photosynthesis Research, 1999)

Selenium, zinc, and thyroid hormones in healthy subjects - Oliviero Olivieri; Domenico Girelli; Anna Maria Stanzial; Luigi Rossi; Antonella Bassi; Roberto Corrocher (Biological Trace Element Research, 1996)